Infrastructure Investment and Industrial Development in Nigeria: The Critical Nexus - O. Olayemi, Simon-Oke (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Many studies have established the critical role played by infrastructure in economic growth and development of nations globally, but relatively few studies have considered the relationship between infrastructure and industrial development. The few studies done in this area especially in Nigeria emphasized the hard core infrastructure-industry relationship. This justifies the study of relationship of both soft and hard core infrastructure with industrial development in Nigeria, using co-integration and error correction mechanism (ECM); with data spanning 1985 and 2015. Findings indicated that all the variables employed in the study contained unit root properties; and were stationary at level. A long run equilibrium relationship was established between infrastructure investment and the index of industrial production in the country. The study also revealed that 12.9% speed of adjustment is required to adjust towards equilibrium in the long run. The study therefore concluded that in the long run investment in both hard and soft core infrastructure would contribute significantly to the level of industrial development in the country, through high quality work force and improvement in life expectancy of average Nigerians.